Crisis in South Korea: From Social Theory to Practices - Cahyo Pamungkas (Journal of Indonesian Social Sciences and Humanities, 2017)
This article aims at describing the way the dimension of the social crisis is within the social sciences and humanities discourses, and the extent such a dimension is noticeable within the crisis reality in South Korea. Literature study of crisis for this study indicates that social crisis is, in theory, a general failure occurring in social life within a historical period, such a crisis produces collective distress generated by the incongruity between the ideas structure and the material structure. The crisis dimension consists of socio-political and socio-economic crises and natural disasters. Available data on the socio-political crisis reality in South Korea displays a fact that those theoretical dimensions are discernible within the Korean society's life since their colonial era until today.